Teori Quantum Learning dan Quantum Teaching serta Implementasinya dalam Pendidikan Islam - Yusi Srihartini; Khairunnisa Khairunnisa; Sohibudin Sohibudin; Dede Alfariz; Ahmad Fauzi; Yuni Nuraeni (El-Mujtama: Jurnal Pengabdian Masyarakat, 2026)
Quantum Learning and Quantum Teaching are innovative educational approaches that emphasize the creation of a positive, meaningful, and engaging learning environment to optimize students’ learning potential. These theories are rooted in cognitive psychology, neuroscience, and constructivist learning principles, focusing on the integration of emotional, physical, and intellectual aspects in the learning process. This study aims to analyze the concepts of Quantum Learning and Quantum Teaching and examine their implementation in Islamic education. Using a qualitative literature review method, this research analyzes various academic sources, including books, journal articles, and relevant educational studies. The findings indicate that the implementation of Quantum Learning and Quantum Teaching in Islamic education can enhance students’ motivation, learning engagement, and academic achievement. Moreover, these approaches align with the values of Islamic education, which emphasize holistic human development encompassing spiritual, moral, emotional, and intellectual dimensions. The application of strategies such as contextual learning, meaningful interaction, positive reinforcement, and active learning contributes to the creation of an effective and student-centered learning environment. Therefore, Quantum Learning and Quantum Teaching are considered relevant and effective approaches for improving the quality of Islamic education in contemporary educational contexts.